Play Therapy Untuk anak-anak Korban Bencana Alam Yang Mengalami Trauma (Post Traumatic Stress Disorder/PTSD) - Endah Nawangsih (Psympathic : Jurnal Ilmiah Psikologi, 2014)
Anywhere in the world, natural disasters events cause loss of life, moreover a deep sorrow and fear for the victims. They were in a state of very uneasy, very scared, never-ending anxiety, and become prone to panic. These conditions called post-traumatic stress disorder (PTSD) as a continuous maladaptive reaction to a traumatic experience. In contrast to adults, children are in a state highly vulnerable to the impact caused by a traumatic event. Children with PTSD may show confusion or agitation. This condition brings suffering prolonged, if not given proper treatment. It required a specific intervention design for children with PTSD namely Play Therapy techniques. This intervention is one way that can be used to understand the world of children through playing, so that when used in the right circumstances can be meaningful as physical activity as well as therapy.